Modelling the effects of habitat and hosts on tick invasions. Issue 1 (14th December 2018) - Nadolny, R. M.; Gaff, H. D.
Abstract: Many tick species are invading new areas because of anthropogenic changes in the landscape, shifting climatic variables and increasing populations of suitable host species and tick habitat. However, the relative influences of habitat and hosts in tick dispersal and tick population establishment remain in question. A spatially explicit agent-based model was developed to explore the spatio-temporal dynamics of a generic tick population in the years immediately following the introduction of ticks into a novel environment. The general model was then adapted to investigate a case study of two recent tick species invasions into the Mid-Atlantic United States. The recent simultaneous range expansions of two ixodid tick species, Ixodes affinis and Amblyomma maculatum, provided an opportunity to determine if invasion patterns observed in the field could be replicated in silico on a small scale. The models presented here indicated that for generalist parasites, habitat connectivity is a better indicator than host mobility for spatial and genetic patterns of parasite range expansion. In addition, our results demonstrate the utility of including genetic variables into agent-based models: gene flow functions as a proxy for measuring dispersal, and models can be validated using results from the field.